Age-at-Onset and APOE-Related Heterogeneity in Pathologically Confirmed Sporadic Alzheimer Disease. (4th May 2021) - Smirnov, Denis S.; Galasko, Douglas; Hiniker, Annie; Edland, Steven D.; Salmon, David P.
Abstract : Objective: To characterize age-related clinical heterogeneity in Alzheimer disease (AD) and determine whether it is modified by APOE genotype or concomitant non-AD pathology, we analyzed data from 1, 750 patients with sporadic, pathologically confirmed severe AD. Methods: In this retrospective cohort study, regression and mixed effects models assessed effects of estimated age at onset, APOE genotype, and their interaction on standardized clinical, cognitive, and pathologic outcome measures from the National Alzheimer's Coordinating Center database. Results: A bimodal distribution of age at onset frequency in APOE ε4− cases showed best separation at age 63. Using this age cutoff, cases were grouped as ε4− early-onset AD (EOAD) (n = 169), ε4+ EOAD (n = 273), ε4− late-onset AD (LOAD) (n = 511), and ε4+ LOAD (n = 797). Patients with EOAD were more likely than patients with LOAD to present with noncognitive behavioral or motor symptoms or nonmemory cognitive complaints, and had more executive dysfunction, but less language impairment on objective cognitive testing. Age at onset and ε4− genotype were independently associated with lower baseline Mini-Mental State Examination scores and greater functional impairment and patients with EOAD had faster cognitive and functional decline than patients with LOAD regardless of APOE genotype. Patients with EOAD were more likely than patients with LOAD to receive a non-AD clinical diagnosis even though they were more likely to have pure AD without concomitant vascular or other non-AD neurodegenerative pathology. Conclusions: Early-onset sporadic AD is associated with a greater likelihood of an atypical, non-memory-dominant clinical presentation, especially in the absence of the APOE ε4 allele, which may lead to misattribution to non-AD underlying pathology.